DETECTION OF MICROBIAL AND CHEMICAL QUALTIY OF SOME CARBONATED DRINKS AND JUICES THAT ARE AVAILABLE IN LOCAL MARKETS - Al- Mossawi, M.; Al-Soufi, M.; Aziz, R. (Iraqi Journal of Science, 2024)
The study was aimed to Detection of microbial and chemical qualtiy for 16 samples of carbonated drinks and juices locally prepared and imported that are available in local markets, the results shows that the canned samples were free from microbial contamination, while the microbial contamination limit of uncanned juices samples P17, P18, P19, P20 were do not fit Iraqi standard specifications and contains coliform bacteria, but did not contains Staphylococcus aureus, Salmonella Spp, Mold and yeast for the anothers samples P5, P6, P7, P8, P9, P10, P11, P12, P13, P14, P15, P16. The results of thin layer Chromatography by silica gel shows no compatible Rf value of the samples P9, P10, P17, P18, P19, P20 with the standard samples that were used for comparison, while full compatible Rf values appears for the anothers samples P5, P6, P7, P8, P11, P12, P13, P14, P15, P16. The results of the optical density using spectrofotometric technique at wave leanth 400 - 600 nm to determine λ max of selected samples P9, P10, P17, P18, P19, P20 were not compatible with the standard samples, while the value of the anothers samples P5, P6, P7, P8, P11, P12, P13, P14, P15, P16 were compatible with the standard samples that used for comparison